Research progress in neuropathic pain after spinal cord injury: a bibliometric study from 2013 to 2024 - Huiqing, Qin; Weishan, Lin; Yuchang, Gui; Yun, Tang; Jianwen, Xu (Frontiers in Neurology, 2024)
BackgroundThe incidence of neuropathic pain (NP) after spinal cord injury (SCI) is quite high. This pain is clinically challenging to treat and has an debilitating effect on patients. In recent years, NP is a popular topic of research and a number of relevant articles have been published in academic journals. The purpose of this article is to analyze the global research trend of NP after SCI using bibliometric methods.MethodsThe literature was screened from 2013 to 2024 based on the Web of Science core collection (WOSCC). These publications, including annual publications, journals, authors, references, and keywords via CiteSpace, were analyzed in order to help understand the current research direction and hotspots in this field.ResultsA total of 2022 publications were included in the analysis. The results showed that an overall upward trend in the number of publications in the study period. The top five productive journals are Spinal Cord, Journal of Neurotrauma, Pain, Experimental Neurology, and Journal of Spinal Cord Medicine, the journals related to spinal cord or pain. The top five most productive scholars are Armin Curt, Michael G. Fehlings, Wu Junfang, John L. K. Kramer, and Farinaz Nasirinezhad. Keyword bursts showed that signaling pathway, neuroinflammation, neuralgia, spinal cord stimulation, inhibition, and depression have become new research hotspots in the field of NP after SCI.ConclusionThis study provides a basis for the study of pain after SCI. It summarizes past research on NP following SCI and offers valuable reference data for further exploration of research trends and issues of focus in this field.